P. D’Mello Road with remnants of the Bombay Port Trust Railway Lines - Mumbai Archive Project Team (Jio Institute, 2024)
Tracks on P. D’Mello Road are remnants of the Bombay Port Trust Railway Lines that were laid in 1915 to transport goods from all the piers and docks to the warehouses, godowns (white building in the background), and storage facilities located along the P. D’Mello Road. This route was also used by the tramway, which first started operation in April 1896 and lasted till March 31, 1964, when all tram services were discontinued in Mumbai.